2022
DOI: 10.1186/s40795-022-00624-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with stunting and thinness among school age children in rural primary schools, East Dembia District, Northwest Ethiopia

Abstract: Purpose To assess the prevalence and factors associated with stunting and thinness among school-age children in rural primary schools in the East Dembia District, Northwest Ethiopia. Methods An institution-based cross-sectional study was conducted using a systematic random sampling procedure to select 840 school-aged children. A structured interviewer-administered questionnaire was used to collect the data. Height and weight measurements were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
4
2
Order By: Relevance
“…It is comparable with other studies conducted in Arba Minch 8.0%, 12 Gondar town northwest Ethiopia 9%, 6 South Gondar Zone, Ethiopia-6.3% 17 and Kallin District, Kafr El-Sheikh Governorate, Egypt 6.7%. 28 However, the finding of this study was lower than those of studies done in Mecha woreda, Amhara regional state, Ethiopia 10.8%, 23 Fogera and Libo Kemkem districts, northwest Ethiopia 21.4%, 7 Ethiopia 18.2%, 24 Dembia district, North West Ethiopia 13% 25 Nsukka, Nigeria 13.0%, 21 Kassala State, Sudan 32.3% 32 and Rural Madagascar 11.2%. 33 The possible reason for this might be seasonal variation and the variability of risk factors across different geographic settings.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…It is comparable with other studies conducted in Arba Minch 8.0%, 12 Gondar town northwest Ethiopia 9%, 6 South Gondar Zone, Ethiopia-6.3% 17 and Kallin District, Kafr El-Sheikh Governorate, Egypt 6.7%. 28 However, the finding of this study was lower than those of studies done in Mecha woreda, Amhara regional state, Ethiopia 10.8%, 23 Fogera and Libo Kemkem districts, northwest Ethiopia 21.4%, 7 Ethiopia 18.2%, 24 Dembia district, North West Ethiopia 13% 25 Nsukka, Nigeria 13.0%, 21 Kassala State, Sudan 32.3% 32 and Rural Madagascar 11.2%. 33 The possible reason for this might be seasonal variation and the variability of risk factors across different geographic settings.…”
Section: Discussioncontrasting
confidence: 73%
“…There is closeness between the sample size in this study and that of study in the Myanmar. However, the study showed that the prevalence of stunting was lower than the study done in Addis Ababa, Ethiopia where 17.8% of the school-age children were stunted,30 Bahir Dar city where 15.13% of the subjects were stunted,13 Northeast Ethiopia where 14.1% were stunted,16 North West Ethiopia where 25.5% of school-age children were stunted25 and urban slums in India where 18.5% of them were stunted 10. When compared with the study done in Arba Minch where 41.9% of the school-aged children were stunted,12 and Gondar town where 46.1% were stunted,6 the prevalence was much lower.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations